The pH of Dental Plaque in Its Relation to Early Enamel Caries and Dental Plaque Flora in Humans - Lingström, P.; Van Ruyven, F.O.J.; Van Houte, J.; Kent, R. (Journal of dental research, 2000)
Dental caries appears to result from the action of multiple, interrelated factors. A companion study dealt with the plaque-flora/caries relationship (van Ruyven et al., 2000). The plaque-pH/caries relationship is the subject of this study. Since both studies involve the same subjects, plaques, and tooth surfaces, data on the examined factors have also been integrated. In vivo plaque pH determinations (microelectrode) were done on buccal sound (s) and "white-spot" (ws) caries surfaces in a selected dentition area in a low-caries (no ws) and higher-caries subject group. The pH response to sugar was evaluated before and after a sugar rinse, a local sugar application, or sucking on a sugary lozenge. pH profiles with sugar rinsing and normal or limited salivary flow conditions, showed progressively decreasing plaque pH values at various time points in the order of: low-caries subjects (s sites), higher-caries subjects (s sites), higher-caries subjects (s + ws sites), and higher-caries subjects (ws sites). The minimum pH values showed the same trend. Analyses of all data indicated only a statistical difference for minimum values for s sites in low-caries subjects vs. ws sites in higher-caries subjects, and for s and ws sites in the latter. Local sugar application and sucking on a sugary lozenge induced smaller pH drops than sugar rinsing; such suboptimal sugar exposure caused a disappearance of the difference between the minimum pH values for s and ws sites observed with sugar rinsing in the higher-caries subjects. Initial plaque pH values were similar regardless of subject or tooth caries status. The values were also not correlated with the plaque levels of strongly iodophilic polysaccharide-storing bacteria. Collectively, both studies indicate that increasing subject caries status is characterized by increasing plaque levels of highly-acid-tolerant, acidogenic bacteria and an increasing plaque-pHlowering potential and support the dynamic relationship between these parameters.